Clinical significance of the “galaxy sign” in patients with pulmonary sarcoidosis in a Japanese single-center cohort - Koide, Takashi; Saraya, Takeshi; Tsukahara, Yayoi; Bonella, Francesco; Börner, Eda; Ishida, Manabu; Ogawa, Yukari; Hirukawa, Ichiro; Oda, Miku; Shimoda, Masafumi; Ohkuma, Kosuke; Fujiwara, Masachika; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: The galaxy sign is an irregularly marginated pulmonary nodule formed by a confluence of multiple small nodules, and it is a diagnostic radiological finding for pulmonary sarcoidosis. However, the clinical significance of the galaxy sign for sarcoidosis has been poorly investigated. Objective: This study aimed to investigate the clinical significance and detailed radiological features of the galaxy sign in patients with pulmonary sarcoidosis. Methods: We retrospectively reviewed 87 patients with biopsy-proven sarcoidosis and 108 patients with pulmonary tuberculosis. Galaxy sign incidence was assessed on thoracic high-resolution computed tomography (HRCT) images from each group. Correlations of galaxy sign with clinical characteristics and disease outcomes were evaluated for patients with sarcoidosis. Results: HRCT findings were available for 65 of 87 patients with pulmonary sarcoidosis and all 108 patients with pulmonary tuberculosis. Galaxy sign incidence was significantly higher in patients with pulmonary sarcoidosis (n=15, 23.1%) than in those with pulmonary tuberculosis (n=2, 1.9%, p<0.001). Among the 65 patients with pulmonary sarcoidosis, those with galaxy signs (n=15) were significantly younger (median: 32 years, interquartile range [IQR] 28-38 years) than those without (n=50) (median: 62 years, IQR 37.7-73 years). The CD4/CD8 ratio in bronchoalveolar lavage fluid (BALF) was also significantly lower in the former group (median: 2.6, IQR 2.0-3.9 vs. median 5.8, IQR 3.7-8.6, p<0.001). Conclusion: Galaxy signs are associated with younger age and low BALF CD4/CD8 ratio but not disease severity.